Inglés express : método acelerado. (Doral, FL : Aguilar, 2011)
Inglés Express teaches English effectively through 100 comprehensive units ordered by grammatical topic and language usage. Each unit is a class in and of itself. With Inglés Express you will feel you have a private tutor right at home! You can determine when and what to study, whether sitting comfortably at home, while driving to work, or in your spare time = Así te enseñamos inglés con INGLÉS EXPRESS!, el curso de inglés que te enseña inglés de una manera directa y efectiva: 100 completas unidades educativas organizadas por temas de interés gramatical y de uso del idioma.
Keywords: English language -- Textbooks for foreign speakers -- Spanish language materials; English language -- Problems, exercises, etc. -- Spanish language materials; Spanish language materials